A systematic study of the dynamics of human communication : with special reference to systems emergent from the Action Frame of Reference - Kapelus, Saville (Rhodes University, Faculty of Humanities, Department of Sociology, 1968)
"Communication" has been described as one of the busiest crossroads in the study of human behaviour. Workers in many disciplines have stressed the importance of knowledge about communication to their own work as well as contributing to the general pool of literature on the various aspects of the subject. Intro., p. 1
Keywords: Communication; Content analysis (Communication)